STRUCTURE FORMATION OF ALKYLAMMONIUM MONTMORILLONITES IN ORGANIC MEDIA - Moraru V.N. (My University, 2001)
Using adsorption, X-ray diffraction (XRD), rheological, electrokinetic, dielectric and calorimetric measurements, the mechanism for the gel formation of the alkylammonium derivatives of the Pyzhevsky montmorillonite (Ukraine) (OM) in organic liquids of different polarity was investigated. The influence of modification, type of the organic cations, length of the alkyl chain, type of organic liquid and polar additive as well as traces of water on the swelling volume, enthalpy of immersion, zeta potential and the Bingham yield stress of the organo-gels were evaluated.